Precise orbit determination of LEO satellites : a systematic review - Selvan, Kannan; Siemuri, Akpojoto; Prol, Fabricio S.; Välisuo, Petri; Bhuiyan, M. Zahidul H.; Kuusniemi, Heidi (Springer, 2023)
The need for precise orbit determination (POD) has grown significantly due to the increased amount of space-based activities taking place at an accelerating pace. Accurate POD positively contributes to achieving the requirements of Low-Earth Orbit (LEO) satellite missions, including improved tracking, reliability and continuity. This research aims to systematically analyze the LEO–POD in four aspects: (i) data sources used; (ii) POD technique implemented; (iii) validation method applied; (iv) accuracy level obtained. We also present the most used GNSS systems, satellite missions, processing procedures and ephemeris. The review includes studies on LEO–POD algorithms/methods and software published in the last two decades (2000–2021). To this end, 137 primary studies relevant to achieving the objective of this research were identified. After the investigation of these primary studies, it was found that several types of POD techniques have been employed in the POD of LEO satellites, with a clear trend observed for techniques using reduced-dynamic model, least-squares solvers, dual-frequency signals with undifferenced phase and code observations in post-processing mode. This review provides an understanding of the various POD techniques, dataset utilized, validation techniques, and accuracy level of LEO satellites, which have interest to developers of small satellites, new researchers and practitioners.
Keywords: Precise orbit determination; Low-Earth Orbit; Global Navigation Satellite Systems; CubeSats; Earth observation; Validation methods; Systematic literature review; Satellite tracking; remote sensing; fi=Automaatiotekniikka|en=Automation Technology|; fi=Tietotekniikka|en=Computer Science|